2021
DOI: 10.3390/ijms221910557
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Affects Olaparib Sensitivity through Induction of Apoptosis in Epithelial Ovarian Cancer Cell Lines

Abstract: This study examined the effect of combination treatment with the poly (ADP-ribose) poly­­merase inhibitor olaparib and metformin on homologous recombination (HR)-proficient epithelial ovarian cancer (EOC). Ovarian cancer cell lines (OV-90 and SKOV-3) were treated with olaparib, metformin, or a combination of both. Cell viability was assessed by MTT and colony formation assays. The production of reactive oxygen species (ROS) and changes in mitochondrial membrane potential were examined using the specific fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Cells were classified as live, apoptotic or necrotic on the basis of their morphological and staining characteristics, and the percentage of specific cellular fractions was determined from the total number of cells. Cells were classified as live (bright blue fluorescence), early apoptotic cells (cells showing intensive blue fluorescence), late apoptotic cells (blue–violet stained cells with concomitant apoptotic morphology), and necrotic cells (red fluorescence) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were classified as live, apoptotic or necrotic on the basis of their morphological and staining characteristics, and the percentage of specific cellular fractions was determined from the total number of cells. Cells were classified as live (bright blue fluorescence), early apoptotic cells (cells showing intensive blue fluorescence), late apoptotic cells (blue–violet stained cells with concomitant apoptotic morphology), and necrotic cells (red fluorescence) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that metformin has weight loss, anti-aging, and anti-cardiovascular effects ( 2 ). In recent years, studies have reported an antitumoral effect of the drug, which has been confirmed in various malignant tumor cells such as liver ( 3 ), ovarian ( 4 ) and lung cancer cells. The present study summarizes knowledge on the anti-tumoral effects of metformin and its mechanism in order to provide evidence for the repurposing of this drug for tumor treatment.…”
Section: Introductionmentioning
confidence: 92%
“…In some experiment systems, metformin can interact with TP53 and have protective effects on lung endothelial cells [ 190 ]. Metformin can affect the sensitivity of ovarian cancer cells which are either mut-TP53 or TP53-null to the poly (ADP-ribose) polymerase (PARP) inhibitor, olaparib [ 191 ]. Decreased levels of AMPK activation (P-AMPK) were detected in PDAC samples as compared to normal tissues.…”
Section: Possibility Of Treatment Of Pdac With Small Molecule Signal ...mentioning
confidence: 99%